Early British Drama in Manuscript - Atkin, Tamara; Estill, Laura (Brepols, 2019)
This collection of essays examines medieval and early modern drama in the context of a rich and varied manuscript culture. Focusing on the production, performance, and reception of dramatic documents made in Britain between 1400 and 1700, the essays in this book shed new light on the role of dramatic manuscripts in a range of different social and literary spheres. From extant manuscripts of England’s mystery cycles to miscellanies kept by seventeenth-century readers, the documents discussed in this volume reflect a culture of producing and using drama in ways that have been overlooked by the recent critical focus on drama and print by theatre historians and literary critics. By showing the various continuities, exchanges, lendings, and borrowings between medieval and early modern scribal practices, as well as between manuscript and print practices, this volume interrogates accepted critical narratives about the way that drama has been historicized.